Interactive Multimedia Development Based on Adobe Flash Cs6 on the Hazards of Free Association - Azharsyah, Al; Valianto, Budi; Novita, Novita; Kasih, Indra (Budapest International Research and Critics University, 2021)
This study aims to develop learning materials on the dangers of promiscuity through interactive multimedia based on Adobe Flash CS6 for class VIII students of SMPN 10 Langsa. This study uses the Brog & Gall development model. The results of the validation include two aspects of the assessment, namely the quality of the learning material by 97.2% then the content of the learning material obtains a result of 88.6 with very good criteria. The results of the feasibility of learning media validation by media design experts were declared